Magnetic Controlled Growing Rods as a Treatment of Early Onset Scoliosis Early Results With Two Patients - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2016)
Study Design. Prospective unicentral nonrandomized study. Objective. To evaluate the safety and effectivity profile of magnetic controlled growing rods (MCGR) in patients with early onset scoliosis (EOS). Summary of Background Data. Conventional growing rods are the most commonly used growth sparring devices in the treatment of EOS, as this technique requires repeated surgical operations for lengthening; it is associated with high rate of complications and increased costs. MCGR in treatment of EOS is effective in correcting deformity whereas allowing continuous spinal growth as reported by a few studies. Methods. A total of 18 patients with progressive EOS were treated by MCGR, two of them had undergone final fusion operation. Patients were followed-up for a minimium time of 9 months from the time of initial surgery. Radiological data were analyzed in terms of Cobb angle, kyphosis angle, T1-T12, and T1-S1 distances in preoperative, postoperative, and last follow up. Results. The mean preoperative Cobb and kyphosis angle were 68 degrees (44-116 degrees) and 43 degrees (98-24 degrees), it was corrected to 35 degrees (67-12 degrees) and 29 degrees (47-21 degrees) immediately after initial operation and maintained at 34.5 degrees (52-10 degrees) and 33 degrees (52-20 degrees) at last follow up, respectively. The mean preoperative T1-T12 and T1-S1 distance were 171 mm (202-130 mm) and 289 mm (229-370 mm), it was increased to 197 mm (158-245 mm) and 330 mm (258-406mm) immediately after initial operation and further increased to 215 mm (170-260 mm) and 357 mm (277-430 mm) at last follow up, respectively. Two patients had undergone final fusion, they had overall mean Cobb angle correction of 668 (62-708), and kyphosis angle change of 538 (26-808). Total height gain in T1-T12 and T1-S1 of 80.5 mm (67-94 mm) and 119 mm (105-133), respectively. Conclusion. MCGR is safe and effective technique in correction of EOS deformity and in maintaining the correction during nonsurgical distraction procedures. A further correction of the deformity and more spinal height gain can be achieved in the final fusion operation.
Keywords: clinical outcome; correction; early onset scoliosis; early results; final fusion; growing spine; height gain; length gain; magnetic growing rod; pediatric spine deformity; sagittal correction; surgical treatment; FOLLOW-UP; SYMPTOMS; CHILDREN; SURGERY